Study of entropy generation and heat flow through a microtube induced by the membrane-based thermofluidics systems. (1st September 2022) - Bhandari, D.S.; Tripathi, Dharmendra
Abstract: A mathematical model to study the thermally fully developed pressure-driven flow of Newtonian fluid in a finite length vertical microtube with a spatial–temporal dependent membrane contraction, is presented. Here, pressure is generated by the membrane propagation and is further regulated by buoyancy forces. Besides, the energy equation refers to the movement of thermal energy between two walls of the microtube. This model examines the kinematics of membrane, flow and pumping characteristics, wall shear stress, Grashof number (Buoyancy force) effects, Nusselt number, isotherms, and entropy generation in the membrane based thermofluidics system. The dimensional analysis followed by the lubrication approach (since radius of the microtube is substantially less than its length) has been utilized to derive the analytical solutions which are further simulated by using the Matlab code for the graphical illustrations. The velocity fields under the effects of thermal properties and membrane kinematics are computed and noted that magnitude to axial velocity increases by 44.8% via the Grashof number in the range 0 to 4. Further, it is observed that the convective heat flow ( N u > 1 ) is performing in the range [ − 0 . 2, 0 . 2 ] due to the rhythmic membrane kinematics. Another side, the membrane shape parameter is a major concern for the entropy generation. Such types of analysis and membrane based thermofluidics could be applicable to control the heat transfer rate and energy in various thermal treatments of biomedical sciences and engineering, and also help to design the thermo-pneumatic micropump. Highlights: A mathematical model for heat transfer in membrane based microtube is presented. The membrane pumping mechanism is highly motivated by insect's respiratory system. The direct heat source increases the temperature elevation up to 49% in microtube. Entropy can be controlled by relative temperature and membrane shape in the system. The findings of the present model are useful in various thermal treatments.